Complexity complicates lean: lessons from seven emergency services. Issue 2 (13th May 2014) - Mazzocato, Pamela; Thor, Johan; Bäckman, Ulrika; Brommels, Mats; Carlsson, Jan; Jonsson, Fredrik; Hagmar, Magnus; Savage, Carl
Abstract : Purpose: – The purpose of this paper is to explain how different emergency services adopt and adapt the same hospital-wide lean-inspired intervention and how this is reflected in hospital process performance data. Design/methodology/approach: – A multiple case study based on a realistic evaluation approach to identify mechanisms for how lean impacts process performance and services' capability to learn and continually improve. Four years of process performance data were collected from seven emergency services at a Swedish University Hospital: ear, nose and throat (ENT) (two), pediatrics (two), gynecology, internal medicine, and surgery. Performance patterns were linked with qualitative data collected through realist interviews. Findings: – The complexity of the care process influenced how improvement in access to care was achieved. For less complex care processes (ENT and gynecology), large and sustained improvement was mainly the result of a better match between capacity and demand. For medicine, surgery, and pediatrics, which exhibit greater care process complexity, sustainable, or continual improvement were constrained because the changes implemented were insufficient in addressing the higher degree of complexity. Originality/value: – The variation in process performance and sustainability of results indicate that lean efforts should be carefully adapted to the complexity of the care process and to the educational commitment of healthcare organizations. Ultimately, the ability to adapt lean to a particular context of application depends on the development of routines that effectively support learning from daily practices.